Introduction: Medical imaging for the quantitative measurement of biophysical parameters - Schaeffter, Tobias; Sack, Ingolf (Springer International Publishing, 2018)
Medical imaging is the backbone of modern clinical diagnosis with the vast majority of images obtained by high-end tomographic modalities such as computed tomography (CT), magnetic resonance imaging (MRI), 3D ultrasound (US), and emission tomography (PET, SPECT). However, the current radiological practice is based on visual inspection of images and most diseases are rated in qualitative terms, which results in limited comparability and accuracy of image-based diagnostic decisions. Therefore, there is a need for quantitative imaging technologies for the assessment of biophysical tissue parameters. This book focuses on imaging approaches to obtain quantitative information of fluid transport, soft tissue mechanics, and tissue structures; and gives examples on clinical applications that benefit from quantitative imaging.
CRIS-Team Scopus Importer:2022-08-03